Pengaruh Pergaulan Teman Sebaya dan Literasi Ekonomi Terhadap Gaya Hidup Hedonisme Mahasiswa Universitas Negeri Makassar - Wulandari, Fitri; Mustafa, Mustafa; Kamaruddin, Syamsu A. (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the influence of peer group interaction and economic literacy on the hedonistic lifestyle of students at Universitas Negeri Makassar. The research employed a quantitative approach with a descriptive design. The population consisted of all students at Universitas Negeri Makassar, with a sample of 83 students selected using the Slovin formula. Data were collected through a closed-ended questionnaire using a five-point Likert scale and analyzed using multiple linear regression. The results indicate that peer group interaction has a positive and significant effect on students’ hedonistic lifestyle, while economic literacy has a negative and significant effect. Simultaneously, peer group interaction and economic literacy significantly influence the hedonistic lifestyle of students. These findings suggest that peer influence plays a role as an external driving factor, whereas economic literacy functions as an internal controlling factor in shaping students’ consumption behavior. Therefore, strengthening economic literacy is essential to reduce the tendency toward hedonistic lifestyles among university students.